KERAGAAN IMPLEMENTASI PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR (PEMP) DI KOTA BENGKULU - Cahyadinata, Indra (Jurnal AGRISEP, 2005)
This research carried out to analyze implementation of PEMP program to coastal community in Engulf Regency. Unit analyze in this research are input, process and output. Human resources as input in implementation PEMP characterized by age 25-65 year, experience 0-40 years and 0-270 workday each years. There is limitation of time in implementation PEMP program, so that processing of inputs become output is in optimal. Economic productive funds (DEP), equal to Rap 1.654.700.000, have been distributed to 395 persons and 3 Spin’s within 4-11 months.